The infant–doctor relationship: an examination of infants’ distress reactions in the presence of a doctor - Motonobu Watanabe; Masaharu Kato; Yoshi-Taka Matsuda; Kosuke Taniguchi; Shoji Itakura (Scientific Reports, 2024)
Abstract Fear of doctors is a common source of distress among infants; however, the underlying sources of this distress are unknown. To investigate the doctor-infant relationship, the behaviors of 61 healthy infants (176–617 days old) were observed in a simulated examination room. Their behaviors and electrocardiograms were recorded. Two groups of infants were analyzed: those who cried and those who did not. When an experimenter dressed in the doctor’s attire entered the room, all 9 infants who were crying (14.8% of all infants) stopped crying, all infants gazed at the experimenter, and their mean heart rate (HR) decreased. After the auscultation started, 29.5% of all infants cried, and the HRs of infants who cried were higher than those of infants who did not cry. During the auscultation, 80.0% of infants who cried averted from the experimenter, while 34.4% of infants who did not cry. Within 5 s of gazing at the stethoscope, the number of infants who cried increased from 3 to 12, and their mean HR also increased. Our findings suggest that the fear of doctors is not due to the appearance of doctors but rather to specific actions performed by doctors, such as auscultation. Infants may regard a doctor’s appearance as a source of interest. Furthermore, a stethoscope is a possible trigger for infants’ crying. These behavioral observations suggest the potential for patient-centered care for infants.